Carrying Concealed Weapons, No. 36, Art. 6, § 3, in The Charter and Revised Ordinances of the City of Palmyra, Missouri 216 (1908) - (:unkn) unknown (My University, 1908)
If any person in this city shall carry concealed upon or about his person any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship or into any school room or place where people are assembled for educational, literary or social purposes, or to any election precinct on any election day, or into any court room during the sitting of court, or into any public assemblage of persons met for any lawful purpose other than for militia drill, or meetings called under the militia law of this State, having upon or about his person any kind of fire-arms, bowie-knife, dirk, dagger, slung-shot, or other deadly weapon or shall, in the presence of one or more persons, exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating, drinks, or shall directly or indirectly, sell or deliver, loan or barter to any minor any such weapon, without the consent of the parent or guardian of such minor, he shall, upon conviction, be punished by a fine of not less than fifty nor more than one hundred and fifty dollars."
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS